The effects of vitamin E or lipoic acid supplementation on oxyphytosterols in subjects with elevated oxidative stress: a randomized trial. Issue 1 (December 2017) - Baumgartner, Sabine; Mensink, Ronald; Haenen, Guido; Bast, Aalt; Binder, Christoph; Bekers, Otto; Husche, Constanze; Lütjohann, Dieter; Plat, Jogchum
Abstract Despite increased serum plant sterol concentrations after consumption of plant sterol enriched margarines, plasma oxyphytosterol concentrations were not increased in healthy subjects. Here, we assessed plasma oxyphytosterol concentrations and whether they are affected by antioxidants in subjects with elevated oxidative stress. Twenty subjects with impaired glucose tolerance (IGT) or type 2 diabetes (DM2) consumed for 4 weeks placebo, vitamin E (804 mg/d) or lipoic acid capsules (600 mg/d). Plasma and blood cell oxyphytosterol and oxycholesterol concentrations were determined in butylated hydroxytoluene-enriched EDTA plasma via GC-MS. Also, markers reflecting oxidative stress and antioxidant capacity were measured. Plasma oxycampesterol and oxysitosterol concentrations were 122% and 83% higher in IGT or DM2 subjects than in healthy subjects, as determined in an earlier study. Vitamin E or lipoic acid supplementation did not reduce plasma oxyphytosterol and oxycholesterol concentrations, or other markers reflecting oxidative stress or antioxidative capacity. Concentrations of different oxyphytosterols correlated within plasma, and within red blood cells and platelets. However, plasma and blood cell oxyphytosterol levels did not correlate. Although plasma oxyphytosterol concentrations are higher in IGT or DM2 subjects than in healthy subjects, 4-weeks vitamin E or lipoic acid supplementation does not lower plasma oxycholesterol or oxyphytosterol concentrations.